Representing the Ring-Net in Word and Image - Lindsay Blair (Angles)
This article sets out to reveal the way that word and image are combined in wholly inventive ways in the work of artist, Will Maclean and poet/historian, Angus Martin. The initial exhibition by Maclean The Ring-Net in 1978, and the publication of Martin’s book The Ring-Net Fishermen in 1981, were their early representations of the world of herring fishing. Their word-image collaborations brought a sensory experience to a new audience: an experience akin, in fact, to the multi-dimensional reality of the ring-net fishermen themselves. The correspondence between the two men during their research period revealed their determination to give absolute priority to the oral testimony of the fishermen above that of any commentators (professional or otherwise) on the industry. The correspondence also signalled the need for the use of both word and image to communicate and transfer information with real accuracy. This article focuses not only on the original Ring-Net research but also on a more recent collaboration where Martin’s poems are set alongside Maclean’s ink drawings in the publication One Time in a Tale of Herring (2010). There are a number of areas of overlap between Maclean’s drawings and the hand-written selection of Martin’s fishing poems. First there is the ‘thingly’ element: the attention above all to nouns and verbs in the poems and the unadorned nature of the drawings; second the phenomenological: the priority given to the sensuous aspects of the fisherman’s experience in the poems and the link to the gestural expressionism of the drawings. Most arresting of all, though, is the way that the image seeks the word and the word seeks the image.